DAMPAK MODERASI PROFITABILITAS TERHADAP PENGARUH CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN MANUFAKTUR - Wulandari, Agusta Amamda; Ramantha, I Wayan; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The incosistency of result of research on the influence of Corporate Social Responsibility for firm value indicate other factors also influencing, so as to encourage researchers to input profitability as moderation variable. The method of sampling technique used on this research is purposive sampling with a sample amount 37 manufacturing companies that listed in Indonesia Stock Exchange (ISE) in year of 2008-2012, and amounting to 174 surveillances. Statistical anaylisis includes the classic assumption test and test the feasibility of this model, and Moderated Regression Analysis (MRA) test used to examine the effect of moderating variable in this research hypothesis. The result of classic assumption test indicates that regression model has just fulfilled the requirement of classic assumption test. The hypothesis test results are: 1) Corporate Social Responsibility has the positive effect on manufacturing firm value listed in Indonesia Stock Exchange, 2) Profitability as moderating variable is proven and capaable to strengthen the relations between Coporate Social Responsibilty with manufacturing firm value that listed in Indonesia Stock Exchange.
Keywords: Corporate Social Responsibility, Profitability, Firm Value